Tumor-Associated Macrophages: Protumoral Macrophages in Inflammatory Tumor Microenvironment - Somaiyeh Malekghasemi; Jafar Majidi; Amir Baghbanzadeh; Jalal Abdolalizadeh; Behzad Baradaran; Leili Aghebati-Maleki (Tabriz University of Medical Sciences, 2020)
Tumor microenvironment consists of malignant and non-malignant cells. The interaction of these dynamic and different cells is responsible for tumor progression at different levels. The non-malignant cells in TME contain cells such as tumor-associated macrophages (TAMs), cancer associated fibroblasts, pericytes, adipocytes, T cells, B cells, myeloid-derived suppressor cells (MDSCs), tumor-associated neutrophils (TANs), dendritic cells (DCs) and Vascular endothelial cells. TAMs are abundant in most human and murine cancers and their presence are associated with poor prognosis. The major event in tumor microenvironment is macrophage polarization into tumor-suppressive M1 or tumor-promoting M2 types. Although much evidence suggests that TAMS are primarily M2-like macrophages, the mechanism responsible for polarization into M1 and M2 macrophages remain unclear. TAM contributes cancer cell motility, invasion, metastases and angiogenesis. The relationship between TAM and tumor cells lead to used them as a diagnostic marker, therapeutic target and prognosis of cancer. This review presents the origin, polarization, role of TAMs in inflammation, metastasis, immune evasion and angiogenesis as well as they can be used as therapeutic target in variety of cancer cells. It is obvious that additional substantial and preclinical research is needed to support the effectiveness and applicability of this new and promising strategy for cancer treatment.